A meta-analysis of the prevalence of bovine trypanosomiasis in some African countries from 2000 to 2018 - Ebhodaghe, F.; Isaac, C.; Ohiolei, J.A. (Preventive Veterinary Medicine, 2018)
Bovine trypanosomiasis is a disease of cattle. In sub-Saharan Africa, the disease mean prevalence estimates are unknown in most endemic countries. We therefore performed a meta-analysis with the aim of estimating national mean prevalence of bovine trypanosomiasis in endemic countries across sub-Saharan Africa. Relevant articles reporting bovine trypanosomiasis prevalence were retrieved through systematic literature search and scanning of articles reference-lists. Eligibility criteria included that articles reported sample size, prevalence, and diagnostic technique adopted. Overall, data from 180 eligible articles from 19 countries satisfied the inclusion criteria. Meta-analysis of prevalence data based on the random-effects model resulted in an overall mean prevalence of 15.10% (95% CI: 13.22–17.08). National prevalence estimates were generally high except those of Benin and Senegal where estimates ranked below 10.00%. Significant heterogeneity (I2 = 98.75%. p = <0.0001) was noted between studies, and univariate meta-regression analysis identified choice of diagnostic method being major contributor to observed heterogeneity (R2 = 36.37%); while country of study (R2 = 9.57%) and sample size (R2 = 3.47%) had marginal effect on heterogeneity. In spite of past and ongoing control activities, bovine trypanosomiasis remains highly prevalent in most endemic sub-Saharan African countries. Nevertheless, dearth of epidemiological data in some countries and the use of less sensitive diagnostic tools limit reliable estimation of the disease prevalence. Therefore, there is the need to intensify efforts in aspects of surveillance and increased application of molecular diagnostic tool(s) across endemic locations as this would raise the chances of achieving a near-accurate estimate of the disease prevalence which is the first step to attempting eradication.
Keywords: Cattle; Trypanosomiasis; Prevalence; Africa